Human telomerase reverse transcriptase binds to a pre-organized hTR in vivo exposing its template - Zemora, Georgeta (Oxford University Press, 2016)
Telomerase is a specialized reverse transcriptase that is responsible for telomere length maintenance. As in other organisms, the minimal components required for an active human telomerase are the template-providing telomerase RNA (hTR) and the enzymatic entity telomerase reverse transcriptase (hTERT). Here, we explored the structure of hTR and the hTERT-induced conformational changes within hTR in living cells. By employing an in vivo DMS chemical probing technique, we showed that the pseudoknot and associated triple helical scaffold form stably in vivo independently of hTERT. In fact, the dimethyl-sulfate (DMS) modification pattern suggests that hTR alone is capable of adopting a conformation that is suited to interact with hTERT. However, in the absence of hTERT the template region of hTR is only weakly accessible to DMS-modifications. The predominant change after binding of hTERT to hTR is the exposure of the template region.